Code-Switching Practices of English Lecturers and Student Attitudes: A Sociolinguistic Case Study at Omna Trisakti Chandra Polytechnic (Academic Year 2024/2025) - Susanto, I Wayan Erik; Basmantra, Ida Nyoman; Ningrum, Ida Ayu Fortuna (COMMUSTY Journal of Communication Studies and Society, 2025)
The aims of the study were 1) to classify the code switching which produced by English Lecturers in teaching English as foreign language in Poltek OTC, 2) to identify types of code switching that were mostly used by the lecturers in teaching English as foreign language in Poltek OTC, 3) to describe the functions of code switching that were produced by the lecturers, 4) to describe the students’ attitude toward the use of code switching in teaching English as foreign language in Poltek OTC. This was qualitative research and the subject of the research were the students and English lecturers in Poltek OTC in academic year 2024/2025. In this study, the data were collected and analyzed by using Interactive Flows of Activities Model adapted from Miles Huberman (1984) The findings showed that the classification of the code switching used by the lecturers were tag, inter-sentential, and intra-sentential code switching. The most type of code switching produced by the lecturers was intra-sentential code switching (42%), followed by tag code switching (38%), and the last was inter-sentential code switching (20%). Regarding to the functions of the code switching, it was found that there were 8 functions, they were regulatory, emphasis, attention, clarification, sociolinguistic play, instruction, reminding, and motivating. The students’ attitude toward the use of code switching was generally positive. Based on the functions of code switching as dimensions in measuring students’ attitude, it was found that the most positive responses given by the students was sociolinguistic play. From 90 students, 86% of the students gave positive responses towards this function, followed by clarification (84%), emphasis (81%), attention (77%), instruction (75%), lexicalization (74%), and the last was regulatory (73%). From the finding above, it could be summed up that the used of code switching by English lecturers in teaching English as a foreign language in Omna Trisakti Chandra Polytechnic was responded positively by the students.